Exploring the Cultivation Path of the "Five Identities" for Teenagers in the New Era - Fu, Xiaofei (Journal of Theory and Practice of Engineering Science, 2023)
Innovating the "Five Identities" education method, cultivating young people to firmly adhere to the "Five Identities", and building a sense of Chinese national community is the noble mission of moral education workers in the new era. Based on the research results of cognitive psychology and educational psychology, this paper actively responds to the opportunities and challenges faced by the "Five Identities" education of adolescents in the new era, and explores the cultivation path of the "Five Identities" of adolescents.